Myocardial Electrotonic Response to Submaximal Exercise in Dogs with Healed Myocardial Infarctions: Evidence for β-Adrenoceptor Mediated Enhanced Coupling during Exercise Testing - del Rio, Carlos L.; Clymer, Bradley D.; Billman, George E. (Frontiers in Physiology, 2015)
Introduction: Autonomic neural activation during cardiac stress testing is an established risk-stratification tool in post-myocardial infarction (MI) patients. However, autonomic activation can also modulate myocardial electrotonic coupling, a known factor to contribute to the genesis of arrhythmias. The present study tested the hypothesis that exercise-induced autonomic neural activation modulates electrotonic coupling (as measured by myocardial electrical impedance, MEI) in post-MI animals shown to be susceptible or resistant to ventricular fibrillation (VF). Methods: Dogs (n = 25) with healed MI instrumented for MEI measurements were trained to run on a treadmill and classified based on their susceptibility to VF (12 susceptible, 9 resistant). MEI and ECGs were recorded during 6-stage exercise tests (18 min/test; peak: 6.4 km/h @ 16%) performed under control conditions, and following complete β-adrenoceptor (β-AR) blockade (propranolol); MEI was also measured at rest during escalating β-AR stimulation (isoproterenol) or overdrive-pacing. Results: Exercise progressively increased heart rate (HR) and reduced heart rate variability (HRV). In parallel, MEI decreased gradually (enhanced electrotonic coupling) with exercise; at peak exercise, MEI was reduced by 5.3 ± 0.4% (or -23 ± 1.8Ω, P<0.001). Notably, exercise-mediated electrotonic changes were linearly predicted by the degree of autonomic activation, as indicated by changes in either HR or in HRV (P < 0.001). Indeed, β-AR blockade attenuated the MEI response to exercise while direct β-AR stimulation (at rest) triggered MEI decreases comparable to those observed during exercise; ventricular pacing had no significant effects on MEI. Finally, animals prone to VF had a significantly larger MEI response to exercise Conclusions: These data suggest that β-AR activation during exercise can acutely enhance electrotonic coupling in the myocardium, particularly in dogs susceptible to ischemia-induced VF.